PENINGKATAN PARTISIPASI DAN HASIL BELAJAR DARING SOSIOLOGI MELALUI PENDEKATAN PROBLEM POSING BERBASIS INFOGRAFIS - Andhy Surya Hapsara (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
The aims of this study is to increase in participation and result of learning among students in sociology online learning by using an infographic-based problem posing approach. Data collection in this class action study conducted by using instruments in the form of observation sheets, formative tests, and questionnaires to obtain students' responses. Subjects of the study were thirty-two students at class XII IPS 1 in SMAN 7 Yogyakarta. Data of the study were presented in percentages per cycle, that were then analyzed to compare the data of each cycle. The results of this study show that the class actions given in the form of the infographic project during the online learning process of sociology can improve participation and result of learning among students. The average of students’ online learning participation in cycle I was 81.51%, while in cycle II it increased to 90.36%. The result of learning was assessed from the level of completedness among students, i.e. 53.13% in cycle I, then it was increase to 90.63% in cycle II. It can be concluded from the study that the application of infographic-based problem posing approach increases participation and result of learning during online learning among students in class XII IPS 1, SMAN 7 Yogyakarta.